Effects of a Diamond Mine on Tundra-Breeding Birds - Smith, Adam C.; Virgl, John A.; Panayi, Damien; Armstrong, Allison R. (ARCTIC, 2010)
Breeding birds (songbirds, shorebirds, and ptarmigan) were surveyed at the Ekati Diamond Mine in Canada’s Northwest Territories from 1996 through 2003. Surveys were conducted on permanent, 25 ha mine and control plots. Five metrics (relative density of individual species, relative density of all birds, species richness using rarefaction curves, and species diversity using two indices) were used to assess potential impacts up to a distance of 1 km from the mine. Six species were more common on mine plots, and three were more common on control plots. Species diversity was slightly higher on mine plots when measured with Fisher’s alpha index. No other metrics suggested strong impacts. This study suggests that the mine has had a relatively limited impact on the upland breeding bird community within 1 km of the footprint but has provided habitat for at least one synanthropic bird species. Further monitoring of breeding birds on the tundra should include pre-development control data and demographic variables such as reproductive success and survival. De 1996 à 2003, on a étudié les oiseaux nicheurs (oiseaux chanteurs, oiseaux de rivage et lagopède) à la mine de diamants Ekati située dans les Territoires du Nord-Ouest au Canada. L’étude a été effectuée sur des parcelles permanentes de 25 ha, situées sur la mine et sur des sites témoins. On a utilisé 5 paramètres de mesure (densité relative de chaque espèce, densité relative de tous les oiseaux, richesse spécifique utilisant les courbes de raréfaction, et diversité spécifique utilisant deux indices) afin d’évaluer les retombées potentielles jusqu’à une distance de 1 km de la mine. Six espèces se retrouvaient plus communément sur les parcelles de la mine, et trois, sur les parcelles témoins. La diversité spécifique était légèrement plus grande sur les parcelles de la mine quand on les mesurait avec l’index alpha de Fisher. Aucun autre paramètre ne laissait croire qu’il y avait des retombées significatives. Cette étude suggère que la mine a eu un effet relativement ...